Использование технологии ретаргетинга для сбора и интеллектуального анализа данных - Валькман, Ю.Р.; Ланбина, А.В.; Потапчук, Е.В. (Моделювання та інформаційні технології, 2010)
This article describes the joint work retargeting and banner network to collect and Mining bottom of the users on the Internet. The advantages of joint operation of these systems.